DIGITAL MARKETING EMPOWERMENT FOR UMKM BUSINESS ACTORS IN TARUMAJAYA DISTRICT, BEKASI REGENCY - Hendrik Ismail Syaleh; Siti Fazria Mamonto; Zainal Dwi Saputra; Hendri Sakoda; Maya Puspita Dewi; Kurniasih Mufidayati (PT. Hasba Edukasi Mandiri, 2025)
With the advancement of technology, digital marketing is an important strategy for the development of Micro, Small, and Medium Enterprises (MSMEs). However, in the Tarumajaya District, Bekasi Regency, many MSMEs still do not utilize the potential of digital marketing to increase competitiveness and product sales. Therefore, the purpose of this study is to provide digital marketing training for local MSMEs with an interactive approach so that participants can directly practice using digital platforms in managing their businesses. The method used in this study is descriptive qualitative and data collection through observation, interviews, and documentation. Despite challenges, such as the still many MSMEs who are not accustomed to using e-commerce platforms, especially those over 40 years old, the results of this study show a significant increase in the understanding and skills of MSMEs in digital marketing.